Case report: A novel heterozygous synonymous variant in deep exon region of NIPBL gene generating a non-canonical splice donor in a patient with cornelia de lange syndrome - Shi, Meizhen; Liang, Yuying; Xie, Bobo; Wei, Xianda; Zheng, Haiyang; Gui, Chunrong; Huang, Rong; Fan, Xin; Li, Chuan; Wei, Xiaojiao; Ma, Yunting; Chen, Shaoke; et al. (Frontiers in Genetics, 2022)
Cornelia de Lange syndrome (CdLS) is an autosomal dominant or X-linked genetic disease with significant genetic heterogeneity. Variants of the NIPBL gene are responsible for CdLS in 60% of patients. Herein, we report the case of a patient with CdLS showing distinctive facial features, microcephaly, developmental delay, and growth retardation. Whole exome sequencing was performed for the patient, and a novel de novo heterozygous synonymous variant was identified in the deep region of exon 40 in the NIPBL gene (NM_133433.4: c. 6819G > T, p. Gly2273 =). The clinical significance of the variant was uncertain according to the ACMG/AMP guidelines; however, based on in silico analysis, it was predicted to alter mRNA splicing. To validate the prediction, a reverse transcriptase-polymerase chain reaction was conducted. The variant activated a cryptic splice donor, generating a short transcript of NIPBL. A loss of 137 bp at the 3' end of NIPBL exon 40 was detected, which potentially altered the open reading frame by inserting multiple premature termination codons. Quantitative real-time PCR analysis showed that the ratio of the transcription level of the full-length transcript to that of the altered short transcript in the patient was 5:1, instead of 1:1. These findings may explain the relatively mild phenotype of the patient, regardless of the loss of function of the truncated protein due to a frameshift in the mRNA. To the best of our knowledge, this study is the first to report a synonymous variant in the deep exon regions of the NIPBL gene responsible for CdLS. The identified variant expands the mutational spectrum of the NIPBL gene. Furthermore, synonymous variations may be pathogenic, which should not be ignored in the clinical and genetic diagnosis of the disease